2022
DOI: 10.1177/00332941221105216
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Styles and Adolescents’ Problem Behaviors: The Mediating Effect of Adolescents’ Self-Control

Abstract: The study examined the mediating role of adolescents’ self-control on the relationship between parenting styles and problem behaviors. A parenting style questionnaire, adolescents’ self-control questionnaire, and the Youth Self-Report were administered to 611 adolescents (335 boys, and 276 girls, Mage = 13.17, SD = 0.46) to assess their parenting styles, self-control, and problem behaviors. The results indicated that paternal rejection was positively associated with externalizing problems and maternal rejectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…In this study, our findings indicate that parenting style was substantially correlated with EBPs among Chinese adolescents, which was in line with other studies [ 59 , 60 ]. According to our results, parental emotional warmth was negatively associated with the EBPs and subscales.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, our findings indicate that parenting style was substantially correlated with EBPs among Chinese adolescents, which was in line with other studies [ 59 , 60 ]. According to our results, parental emotional warmth was negatively associated with the EBPs and subscales.…”
Section: Discussionsupporting
confidence: 93%
“…Despite accumulating studies regarding the parental socialization of adolescent prosocial behavior, research in non-Western countries is scarce, and only limited research has examined the role of parental marital quality in this process. To date, only one study has shown that parental marital quality is a significant predictor of Chinese adolescent prosocial behavior [6]. In the present study, we examine the relationship between parental marital quality and adolescent prosocial behavior to better understand this important phenomenon.…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies have emphasized the role of parenting behaviors (i.e., authoritative parenting, acceptance, or harsh parenting) in fostering prosocial development in youth [4,5]. In addition, evidence has recently accumulated to suggest that parental marital quality is a strong predictor of prosocial behavior [6,7]. Marital quality is the key antecedent of parenting practice, which ultimately contributes to children's socialization outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Suboptimal parenting constitutes another set of environmental experiences that may influence both stress and self-control around alcohol. In fact, a recent study identified self-control as a mediator in the relationship between parenting styles and problematic behavior [77]. Yet, no prior research has considered relationships among parenting styles, stress, and IC.…”
Section: Stress and Impaired Control Over Drinkingmentioning
confidence: 99%